In vitro evaluation of antiviral activity of essential oil from Zataria multiflora Boiss. against Newcastle disease virus - Mohammadi Ali; Mosleh Najmeh; Shomali Tahoora; Ahmadi Maryam; Sabetghadam Sara (Shahrekord University of Medical Sciences, 2015)
Introduction: The study aimed to investigate the antiviral activity of Zataria multiflora (ZM) essential oil against Newcastle disease virus (NDV) on Vero cells. Methods: The cytotoxicity of ZM essential oil was evaluated by MTT assay. Cells were infected with 100 TCID50 of a field isolate of virulent NDV (JF820294.1). ZM essential oil at concentrations of 1/5000, 1/25 000, 1/125 000 or 1/625 000 was added at different times of infection: 60 minutes pre infection, simultaneously and 60 minutes post infection. Cells were evaluated morphologically. The TCID50, neutralizing index (NI) and HA titer were determined. Results: Cells treated with ZM essential oil in all concentrations 1 hour before or after infection, showed CPE similar to control virus cells. In simultaneous use, cells treated with 1/5000 concentration of the essential oil, remained morphologically normal. TCID50 values of all treatments were very close to that of control virus except for simultaneous administration at concentration of 1/5000 which was about 1000 folds lower. Virus titer in different treatments was exactly the same as control virus titer in Haemagglutination (HA) test. Conclusion: ZM essential oil has some antiviral activity on NDV in vitro, which is possibly by destruction of virus infectivity or inhibition of early phases of viral proliferation cycle.